Personality and work – Life Balance - Chitra Devi, A.; Sheela Rani, S. (Journal of Contemporary Research in Management (JCRM), 2013)
Interference between the work and family domains is considered to be one f the 10 major problems in the work place. Work – family interference may arise when work demands absorb time and create strain that makes adequate functioning in the family domain more difficult. This generally results in work-life imbalance. The imbalance may have several detrimental consequences for organizations, individual workers and their family. It has also been linked to decreased job satisfaction, life satisfaction, worker productivity and organizational commitment likely to increase absenteeism and turnover. This paper examines the impact of personality on work-life balance. It analyses the individual differences in maintaining a proper balance between work and non-work domains, mainly caused by the personality using ‘Big Five’ personality model. The impact of age and designation on work-life balance is also studied. A survey is conducted among 300 women employees working in Business Process Outsourcing (BPO) Organizations at Chennai. The findings of the study suggest that there is no significant relationship between openness to experience, conscientiousness, extroversion and emotional stability and work-life balance but a positive correlation is found to exist between agreeableness and work-life balance. Significant difference is observed in the level of work-life balance of the respondents elonging to various age groups and designations.